Disseminação de Pseudomonas aeruginosa em diferentes regiões do Brasil: Resistência a Carbapenêmicos, Virulência e o Impacto do Uso de Antimicrobianos - Almeida, Vitelhe Ferreira (2025)
Pseudomonas aeruginosa is classified as a high-priority microorganism by the World Health Organization. It remains one of the most challenging pathogens to control in hospital environments, primarily due to its intrinsic resistance to various classes of antimicrobials and its exceptional capacity to acquire additional resistance and spread rapidly. The outlook for controlling the dissemination of this microorganism in diverse environments within low-and middle-income countries is concerning. This study provides data on risk factors predisposing individuals to infections by multidrug-resistant (MDR) P. aeruginosa, biofilm formation, virulence associated with the Type III Secretion System, and the spread of high-risk clones carrying the blaKPC-2 gene. Initially, an epidemiological study was conducted, involving retrospective study of MDR-P. aeruginosa infection cases and their relationship with antimicrobial use. Subsequently, molecular analyses included determining clonal profiles, identifying relevant resistance and virulence genes with endpoint-PCR, and assessing the expression of target genes related to beta-lactams, fluoroquinolones, aminoglycosides, and porins by qRT-PCR. The blaKPC gene was sequenced, and clonal dissemination was assessed through PFGE and MLST. Epidemiological data indicated that prior indiscriminate use of antimicrobials and intrinsic risk factors were associated not only with an increase in MDR strains in hospitals but also with the unfavorable prognosis of patients infected with MDR strains. Notably, a significant frequency of P. aeruginosa strains exhibited both the exoU and exoS genes, with a high percentage carrying the blaKPC-2 (14%) and blaPDC-5 (64%) genes across two distinct clonal profiles disseminated in different regions of the same city in the Triângulo Mineiro region. ExoU-producing strains were associated with MDR, and 78% of the 15 strains tested demonstrated biofilm-forming capacity. In a subsequent phase involving 87 carbapenem-resistant P. aeruginosa strains from various regions of the country, primarily from tracheal infections (65%), high frequencies of the blaPDC-5 (88%), blaKPC-2 (12%), and blaOXA-48 (4%) genes were observed. No overexpression of efflux pumps, blaPDC-5, or ampC genes was detected compared to the control strain (PAO1), and no reduction in oprD gene expression was observed. MLST analysis revealed that all tested strains (9%) belonged to novel sequence types (STs) associated with five clonal complexes (CC): CC27 (ST5044), CC155 (ST5038), CC244 (ST5037, ST5040, ST5043), CC235 (ST5039), CC277 (ST5041), and CC639 (ST5042). Notably, three of these samples belonged to the high-risk clonal complex CC244 (PA06H, PA23H, PA01M), and cross- transmission was observed among strains recovered in the northeastern region of the country. This study provides valuable data on healthcare-associated infections by MDR-P. aeruginosa and their relationship with antimicrobial use in infections with poor prognoses. Additionally, it highlights the spread of multiple virulent MDR P. aeruginosa clones, biofilm producers carrying the blaKPC-2 gene. Notably, eight novel STs with dissemination potential were identified, among the top 10 high-risk clones spread globally.